Osmoderma eremita (Coleoptera, Scarabaeidae, Cetoniinae) in Europe - Ranius, T. (Animal Biodiversity and Conservation, 2005)
Research, monitoring and development of preservation strategies for threatened species are often limited by national borders even though a global perspective would be more appropriate. In this study, we collected data on the occurrence of a threatened beetle, Osmoderma eremita, associated with tree hollows in 2,142 localities from 33 countries in Europe where it is or has been present. The larvae develop in tree hollows and very few observations of larvae have been observed in dead logs on the ground. As long as there is a suitable tree hollow, it appears that O. eremita may use any tree species. Oaks (Quercus spp.) are the trees mainly used by O. eremita, followed by lime (Tilia spp.), willow (Salix spp.), beech (Fagus sylvatica) and fruit trees (Prunus spp., Pyrus spp., Malus domestica). O. eremita is still found in some remnants of natural forest, but is mainly observed on land that has long been used by man, such as pasture woodlands, hunting parks, avenues, city parks and trees around agricultural fields and along streams. The occurrence of O. eremita seems to have decreased in all European countries. Relatively high densities of O. eremita localities occur in Central Europe (northern Italy, Austria, Czechia, southern Poland and eastern Germany), some parts of Northern Europe (south-eastern Sweden, Latvia) and France. In some regions in north-western Europe, the species is extinct or may occur at some single sites (Norway, Danish mainland, The Netherlands, Belgium, north-eastern France). There are few data from south-eastern Europe. Many local extinctions of O. eremita are to be expected in the near future, especially in regions with recent habitat loss and fragmentation. O. eremita is useful as an indicator and umbrella species for the preservation of the entire invertebrate community associated with hollow trees in Europe. A preservation plan for O. eremita should include three aspects that are of general importance in nature conservation in Europe today: (1) preservation of remnants of natural forests with old, broad-leaved trees, (2) preservation and restoration of habitats related to traditional agricultural landscapes and (3) preservation of remaining ‘islands’ of nature in urban areas.